Disappearance of codeine, morphine and 6-MAM in hair after cessation of abuse - Suárez-García, A.; Álvarez-Freire, I.; Bermejo-Barrera, A.M.; Cabarcos-Fernández, P.; Tabernero-Duque, M.J. (Forensic science international, 2023)
Research on the determination of drugs of abuse in hair has established that drugs can be detected in hair even long after cessation of use. The purpose of this study was to analyze hair samples from chronic opioid users who were beginning a controlled drug cessation program. The study population (n = 15) is involved in a drug rehabilitation program in Santiago de Compostela, Spain. Over a 6-month period, subjects provided hair samples at 2-month intervals, with the first sample collected on the day they began the program. Codeine, morphine, and 6-MAM were analyzed by GC/MS (LOQ = 0.2 ng/mg). Hair tresses were divided into 1 cm segments and analyzed for all analytes 0–1 cm corresponding to the proximal portion to the scalp Following cessation of opioid use, traces of codeine, morphine, and 6-MAM still remained in the newly growing hair segments for a specified period. After 2 months, still 27 % of the users tested positive, and at 4 months, 20 % were positive but only for 6-MAM. However, after 6 months of abstinence, the results were negative for all analytes. •Hair samples are useful for monitoring drug use.•Hair samples from people who entered a drug cessation program were used.•Through analysis by hair segments, the disappearance time of opioids (6-MAM, morphine and codeine) is evaluated.•6 months are necessary from the cessation of consumption to ensure the total negativity of the hair sample to opioids.